ChatGPT (AI) Integration in Teaching and Learning: Opportunities and Challenges - Oranga, Josephine; Matere, Audrey; Ndaita, Justina (Technium Education and Humanities, 2024)
As studies about artificial intelligence (AI) in the education sector increase, some scholars believe that teachers’ roles in instruction-delivery may change drastically. This conceptual paper, thus, sets out to establish the role, benefits and challenges that are associated with the utilisation of ChatGPT (Generative Pre-trained Transformer) in learning. Ultimately, this analysis reveals that while generally ChatGPT has benefits, it has a number of drawbacks too. Consequently, the advantages and benefits of ChatGPT in learning as discussed in this chapter include: provision of instant feedback, audio-language tutoring, offers interactive learning, helps brainstorm ideas on new topics, enables automatic test-grading, offers personalised tutoring and provides lesson-preparation assistance to educators. On the other hand, the drawbacks of ChatGPT include: integrity and ethical issues, interferes with students’ development of core-competencies/skills, leads to over-reliance on AI, generation of inaccurate information and unfair assessment of learning/ learners. It is thus, recommended that instructors and teachers supervise the integration of ChatGPT in learning environments and guide learners on how and when to utilize the programme. Accordingly, proper acknowledgement should be an integral part of ChatGPT utilisation in learning and research.